Moisturizing and antioxidant evaluation of Moringa oleifera leaf extract in topical formulations by biophysical techniques - Álvarez-Román, R. (2020)
The phytochemical profile, formulations (nanoparticles and gel), moisturizing and antioxidant potential of a hydroalcoholic fraction of Moringa oleifera leaves (HFM) were determined. These were obtained through the application of eco-friendly strategies of cultivation and processing. The HFM phytochemical analysis by ESI-IT-MSn showed the presence of seven compounds (flavonoids and phenolic acids). The viscosity, pH and particle size of HFM formulations ensure the suitability for topical application. Antioxidant activity was determined by inhibition of lipid peroxidation and ferric thiocyanate in vitro; it was confirmed that HFM and in formulations showed a significant inhibition of oxidation. In relation to the in vitro skin biophysical evaluation for topical formulations of HFM, water content, lipids and trans-epidermal water loss on the skin were favored with the presence of HFM. In addition, skin pH was not been modified. Our results emphasize the moisturizing and antioxidant potential of the moringa-formulation as a new skin drug delivery system.